Endogenous market structures and financial development - Zsolt Becsi; Ping Wang; Mark A. Wynne (Federal Reserve Bank of Atlanta, 1998)
Existing theories that emphasize the significance of financial intermediation for economic development have not addressed two important empirical facts: (i) the relationship between financial and real activities depends crucially on the stage of development, and (ii) financial and industrial market structures vary widely across otherwise similar countries. To explain these observations, we develop a dynamic general equilibrium model allowing for endogenous market structures in which financial deepening spurs real activity through intermediate product broadening. We show the possibility of multiple steady-state equilibria and characterize how these equilibria respond to various shocks. In particular, we examine the determinants of financial deepening, product broadening, the saving rate, the loan-deposit interest rate spread, and the degree of competitiveness of financial and product markets. We find that the dynamic interactions between financial and real activities depend critically on the synergy of financial and industrial competitiveness.
Keywords: 330; Economic development